1983
DOI: 10.1007/bf01338888
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a combination of X-rays and caffeine on preimplantation mouse embryos in vitro

Abstract: The influence of a combination of caffeine (0.1 mM, 1 mM, or 2 mM) and X-rays (0.24 Gy, 0.94 Gy, or 1.88 Gy) on preimplantation mouse embryos in vitro was studied under different conditions. The agents were applied either singly or in combination. The embryos were irradiated in the G2-phase of the two-cell stage (28 h p. c. or 32 h p. c.) either 1 h after or immediately before application of caffeine. Caffeine was present during the whole incubation period (until 144 h p. c.). The effects on the microscopic vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The failure of caffeine to enhance 3H-thymidine-induced SCEs in our experiments is probably not due to the concentration of caffeine used (1 mM), because an enhancement of a number of effects induced by ionizing radiation has been detected in the presence of caffeine at similar concentrations [28]. Caffeine (0.5-2 mM) and X-rays had supra-additive effects on preimplantation development in mouse embryos in vitro [29] and on micronuclei formation 1301. An enhancement of UV effects by caffeine (0.1-0.5 mM) on blastocyst formation has also been reported [15].…”
Section: Discussionmentioning
confidence: 53%
“…The failure of caffeine to enhance 3H-thymidine-induced SCEs in our experiments is probably not due to the concentration of caffeine used (1 mM), because an enhancement of a number of effects induced by ionizing radiation has been detected in the presence of caffeine at similar concentrations [28]. Caffeine (0.5-2 mM) and X-rays had supra-additive effects on preimplantation development in mouse embryos in vitro [29] and on micronuclei formation 1301. An enhancement of UV effects by caffeine (0.1-0.5 mM) on blastocyst formation has also been reported [15].…”
Section: Discussionmentioning
confidence: 53%
“…The examination of our results by an isobologram analysis revealed that there is an interaction between caffeine and X-rays. Thus the results obtained in this study are in agreement with our results that combinations of caffeine and X-rays lead to supraadditive effects with respect to the morphological development and to the cell numbers of mouse embryos [36].…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge is also necessary for the prediction of caffeine effects at low concentrations. The experimental systems only allow analyses at unrealistic high concentrations [corresponding to several hundred cups of coffee or tea per day (MUller et al, 1983)].…”
Section: Discussionmentioning
confidence: 99%